Percepção da qualidade de vida e satisfação no trabalho: um levantamento de acadêmicos de um Curso de Administração no Norte do RS - Martins, Jéssica Gugiel (2023)
This article analyzed the perception of quality of life and satisfaction in the work environment of students on an Administration course in the North of RS. The research that underpins this study has a qualitative and exploratory approach, consisting of data collection carried out through questionnaires applied to academics, which consists mainly of open questions, but there are also closed questions, for Gil (2019) open questions allow for broad freedom of response. The questionnaire was prepared using Google forms, made available through social media and networks (e-mails and Whatsapp groups) and sent to all students of the Administration Course, with 45 completed questionnaires returned. References were sought from authors with knowledge of content analysis. Bardin (1977, p.45) defines content analysis as “an operation or set of operations aimed at representing the content of a document in a form different from the original in order to facilitate its consultation and referencing at a later stage”. According to the perception of the responding academics, the main positive aspects of the work are: a) Good Work Environment, b) Good Salary, c) Benefits, d) Flexibility e) Opportunity for Growth, f) Teamwork, g) Organization. The main negative aspects of the work are: a) Difficulty in Communication, b) Many Charges c) High Demand, d) Bureaucracy. Companies are looking for quality of life and employee satisfaction, but it is still necessary to invest in communication and hiring to reduce demand and, consequently, pressure.